THE EFFECTIVENESS OF THE PROBLEM BAESD INSTRUCTION MODEL WITH VIDEOS ON CRITICAL THINKING ABILITIES OF SENIOR HIGH SCHOOL 1 MAYONG STUDENTS - Mauludah, Nurul; Peniati, Endah; Widiyaningrum, Priyantini (FMIPA UNNES, 2019)
The ability to think critically is needed in the 21st century so that students must have the ability to think critically.Withthese abilities, students are more able to master the concept of material, able to provide further explanation and provide alternative problem-solving so that students are expected to be able to solve problems in the environment in the future. This study aims to analyze the problem-based instruction model with effective video applied to senior high school 1 Mayong students on the ability to think critically and analyze the problem-based instruction model with video so that it can improve the critical thinking skills of senior high school 1 Mayong students. This study used pre-experimental design with one group pretest-posttest design. The sample of this study were students of class XI MIPA 3 and XI MIPA 4 Senior High School 1 Mayong which were determined using purposive sampling technique. The independent variable is a problem-based instruction model with an immune system video media. Dependent variables besides critical thinking skills are also conservation attitudes that are expected to arise during the learning process. The researcher collected the data using test questions and observation sheets. The results of data analysis showed that students' critical thinking skills reached 92.5% completeness. On average, every aspect of students' critical thinking skills are in critical and very critical criteria and the average conservation value of students is honest, creative and humanist in good, good and very good criteria. The average N-gain in both classes is included in the criteria of medium (0.69) and high (0.71). Based on the results of the study, it can be concluded that the problem-based instruction model with effective video is applied to senior high school 1 Mayong students towards critical thinking skills and problem-based instruction models with videos can improve the critical thinking skills of senior high school 1 Mayong students